Commonwealth Declaration for Empowerment of Junior Doctors - Karthikeyan, Venkatesh; Jayalal, Johnrose Austin; Hariharan , VS; Hasan, KM Abul; Joshi, Shiv; Shazellenne, Merlinda; Raj , Duane Muruga; Deshmukh, Indranil; Porter, Pablo Estrella; Aggarwal, Pradeep (Indian Journal of Community Health, 2025)
We, the representatives of Junior Doctors from National Medical Associations (NMAs) across the Commonwealth, assembled in Chennai, India, during the 27th Biennial Conference of the Commonwealth Medical Association – on 9th November 2024, acknowledge the vital contributions of junior doctors in delivering healthcare and the unique challenges they encounter in their early careers. This Commonwealth Declaration for Junior Doctors reaffirms our unified commitment to the well-being, growth, and resilience of junior doctors, recognizing their critical role as the backbone of healthcare systems. Grounded in the principles of equity, dignity, and empowerment, this Declaration aims to create supportive environments that safeguard the mental and emotional health of junior doctors, foster personal and professional development, and build their leadership capacity. With this Declaration, we call upon Governments, Health Institutions, and Professional Bodies across the Commonwealth to prioritize initiatives that address workplace violence, foster healthy work environments, and expand career and training opportunities within and beyond borders. We also advocate for strengthening mentorship, promoting research, supporting medical entrepreneurship, and building exchange programs to help junior doctors embrace family medicine, primary healthcare, and community-oriented practices. This collective commitment ensures a nurturing environment for junior doctors that will strengthen healthcare systems and enhance the well-being of communities across the Commonwealth.